A method for detecting the crosslinking degree of the insulation layer of ultraviolet crosslinked cable
By using soldering iron on the ultraviolet cross-linking cable for cross-sectional pressure detection, the problem of insufficient cross-linking is solved, the detection process is simplified, the efficiency is improved, and the product quality is ensured. It is suitable for fast and accurate detection of ultraviolet cross-linking. Crosslinking degree of cable insulation layer.
Patent Information
- Application Number
- CN202210484472.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-05-06
AI Technical Summary
When producing crosslinking polyethylene insulated cables, the ultraviolet light crosslinking process has problems with insufficient crosslinking, resulting in unqualified product quality and safety hazards. The existing detection methods take a long time, affecting efficiency and cost.
By taking samples at both ends of the ultraviolet crosslinking cable to be tested, using a soldering iron to press the cross section multiple times until the entire cross section is pressed, we can determine whether the deformation can be restored after each soldering pressure to determine the crosslinking degree. Qualified or not.
This method simplifies the inspection process, reduces operation difficulty, saves time, improves inspection efficiency, ensures product quality, eliminates the phenomenon of unqualified insulation cross-linking, and reduces losses to cable manufacturers.
Smart Images

Figure BDA0003628696470000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultraviolet cross-linked cables, in particular to a method for detecting the cross-linking degree of an insulation layer of an ultraviolet cross-linked cable. Background Art
[0002] The UV cross-linking process is used for the production of cross-linked polyethylene insulated cables with a rated voltage of 3kV and below. It has the advantages of high efficiency and energy saving, green environmental protection, high production efficiency, space saving, and lower cost than the silane cross-linking process. It is favored by more and more cable companies, and many cable companies have adopted this production process.
[0003] However, when using the UV cross-linking process to produce cross-linked polyethylene insulated cables, there is a problem that has not been well solved so far: when the operator controls improperly (such as excessive jitter when the two ends of the wire core pass through the cross-linking device, the speed exceeds the process speed, the local failure of the UV cross-linking machine is not discovered in time, and the surface pollution of the UV lamp is not effectively removed in time, etc.), the insulation layer will be partially cross-linked insufficiently, and the cross-linking index will be unqualified, specifically, the elongation under load during the hot extension test is greater than 175%, and the permanent deformation rate is greater than 15%. This will cause the product quality to fail to meet the standard requirements, there are safety hazards, and in severe cases, power supply accidents will occur. Moreover, this defect of insufficient cross-linking is often difficult to remedy, or the cost of remediation is too high, resulting in large losses for cable companies.
[0004] In addition, the insufficient cross-linking caused by the UV cross-linking process is different from the insufficient cross-linking caused by chemical cross-linking or silane cross-linking. In both cases, the cross-linking degree of the entire insulating layer is unqualified, while the insufficient cross-linking caused by the UV cross-linking process may result in the cross-linking degree of the entire insulating layer being unqualified, or only part of the entire insulating layer cross-section being unqualified. It has been found that only about 10° (the entire insulating layer cross-section is defined as 360°) of the insulating layer has an unqualified cross-linking degree, and this situation cannot be detected by quality assurance personnel according to inspection regulations, so unqualified products will still flow out.
[0005] Due to this problem, the promotion and application of UV cross-linking technology is subject to certain limitations. It even leads to some cable manufacturers to reject UV cross-linking technology. However, the advantages of UV cross-linking technology still attract many cable companies. Therefore, in order to ensure the quality of factory products, many companies have strengthened the process control of the insulation process and the inspection of insulation cross-linking degree, and listed the cross-linking degree inspection as a routine test for finished cables when they leave the factory, and the cross-linking degree test is carried out on the four sides of the annular insulation layer of each insulation core. This increases the difficulty of operation for operators and inspectors and reduces the efficiency of finished product inspection. In addition, the method specified in the current standard (GB / T2951.21-2008 "General Test Methods for Insulation and Sheath Materials of Cables and Optical Cables Part 21: Special Test Methods for Elastomer Mixtures-Ozone Resistance Test-Hot Extension Test-Mineral Oil Immersion Test") is used for testing. A hot extension test takes at least 15 minutes. If the four sides of the insulation core are tested, it takes at least 20 minutes, which has a great impact on the cost and efficiency of the enterprise. Therefore, there is an urgent need for a method that can quickly and accurately detect the crosslinking degree of the UV-crosslinked cable insulation layer. Summary of the invention
[0006] The purpose of the present invention is to provide a method for detecting the crosslinking degree of the insulation layer of an ultraviolet crosslinked cable. The detection method provided by the present invention is simple to operate, saves time, and can ensure product quality.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for detecting the crosslinking degree of an ultraviolet crosslinked cable insulation layer, comprising the following steps:
[0009] (1) Sampling at both ends of the UV-crosslinked cable to be tested to obtain a sample to be tested;
[0010] (2) using an electric soldering iron to perform soldering and pressing on the cross section of the sample to be tested obtained in step (1) for multiple times until the entire cross section of the sample to be tested has been pressed;
[0011] If the deformation caused by each soldering pressure on the cross section of the sample to be tested can be restored immediately after the soldering iron is removed, the cross-linking degree of the UV light cross-linked cable insulation layer to be tested is judged to be qualified; if the deformation caused by each soldering pressure on the cross section of the sample to be tested cannot be restored at least one place after the soldering iron is removed, the cross-linking degree of the UV light cross-linked cable insulation layer to be tested is judged to be unqualified.
[0012] Preferably, the cross-sectional area of the sample to be tested in step (1) is 25 to 500 mm 2 .
[0013] Preferably, the temperature of the electric soldering iron in step (2) is 270-280°C.
[0014] Preferably, during each soldering in step (2), the electric soldering iron stays on the cross section of the sample to be tested for 5 to 8 seconds.
[0015] Preferably, the pressure of each pressing in step (2) is 1 to 1.5N.
[0016] Preferably, the multiple pressing steps in step (2) include: performing a first pressing step on the cross section of the sample to be tested, and then changing the pressing position for the next pressing step, so that the angle formed by the positions of the Nth pressing step and the N-1th pressing step is ≤30°.
[0017] Preferably, in the step (2), the method for determining whether the deformation of the sample to be tested cannot be restored is as follows: the difference in thickness between the sample to be tested after the electric soldering iron is removed and before soldering is ≥1 mm.
[0018] The present invention provides a method for detecting the crosslinking degree of the insulation layer of an ultraviolet crosslinked cable, comprising the following steps: (1) sampling at both ends of an ultraviolet crosslinked cable to be tested to obtain a sample to be tested; (2) using an electric soldering iron to perform soldering and pressing on the cross section of the sample to be tested obtained in step (1) for multiple times until the entire cross section of the sample to be tested is pressed; if the deformation generated on the cross section of the sample to be tested after each soldering and pressing can be immediately restored after the electric soldering iron is removed, it is determined that the crosslinking degree of the insulation layer of the ultraviolet crosslinked cable to be tested is qualified; if at least one of the deformation generated on the cross section of the sample to be tested after each soldering and pressing cannot be restored after the electric soldering iron is removed, it is determined that the crosslinking degree of the insulation layer of the ultraviolet crosslinked cable to be tested is unqualified. The present invention takes samples at both ends of the UV cross-linked cable to be tested, and then uses an electric soldering iron to solder it for multiple times until the entire cross section of the sample to be tested is pressed, and finally determines whether the cross-linking degree of the insulation layer of the UV cross-linked cable to be tested is qualified by judging whether the deformation generated after each soldering on the cross section of the sample to be tested can be restored after the electric soldering iron is removed, which greatly reduces the operating difficulty of operators and inspectors, saves time, improves the efficiency of finished product inspection, and can ensure product quality, completely eliminating the phenomenon of unqualified insulation cross-linking degree. The results of the embodiment show that the detection method provided by the present invention is used to detect the UV cross-linked cable, and it takes a total of 5 minutes from sampling to result confirmation, and the detection result is consistent with the result of testing using the standard method.
[0019] The method for detecting the crosslinking degree of the UV crosslinked cable insulation layer provided by the present invention can reduce the adverse effects of the UV crosslinking process on cable production enterprises to a minimum, and is conducive to the promotion and application of the UV crosslinking process. DETAILED DESCRIPTION
[0020] The present invention provides a method for detecting the crosslinking degree of an ultraviolet crosslinked cable insulation layer, comprising the following steps:
[0021] (1) Sampling at both ends of the UV-crosslinked cable to be tested to obtain a sample to be tested;
[0022] (2) using an electric soldering iron to perform soldering and pressing on the cross section of the sample to be tested obtained in step (1) for multiple times until the entire cross section of the sample to be tested has been pressed;
[0023] If the deformation caused by each soldering pressure on the cross section of the sample to be tested can be restored immediately after the soldering iron is removed, the cross-linking degree of the UV light cross-linked cable insulation layer to be tested is judged to be qualified; if the deformation caused by each soldering pressure on the cross section of the sample to be tested cannot be restored at least one place after the soldering iron is removed, the cross-linking degree of the UV light cross-linked cable insulation layer to be tested is judged to be unqualified.
[0024] The invention takes samples at both ends of the ultraviolet light cross-linked cable to be tested to obtain the sample to be tested. The invention ensures the accuracy of the test result by taking samples at both ends of the ultraviolet light cross-linked cable to be tested.
[0025] In the present invention, the detection of the crosslinking degree of the UV-crosslinked cable insulation layer is preferably carried out on a production line. In the present invention, the UV power on the production line is preferably 90-92%; the line speed of the production line is preferably 15-70 m / min.
[0026] The detection method provided by the present invention is suitable for testing the crosslinking degree of various UV crosslinked cable insulation layers. In the present invention, the UV crosslinked cable to be tested preferably includes a copper core crosslinked polyethylene insulation core, an aluminum core crosslinked polyethylene insulation core or a copper core fire-resistant crosslinked polyethylene insulation core.
[0027] In the present invention, the cross-sectional area of the sample to be tested is preferably 25 to 500 mm 2 , more preferably 70 to 300 mm 2 .
[0028] After obtaining the sample to be tested, the present invention uses an electric soldering iron to perform multiple soldering and pressing on the cross section of the sample to be tested until the entire cross section of the sample to be tested is pressed. The present invention ensures the comprehensiveness of the test result by performing multiple soldering and pressing on the cross section of the sample to be tested.
[0029] In the present invention, the temperature of the electric soldering iron is preferably 270-280° C., more preferably 270-275° C. In the present invention, the temperature of the electric soldering iron is preferably controlled within the above range to allow the sample to be fully deformed. In the present invention, the electric soldering iron is preferably an automatic temperature control electric soldering iron.
[0030] In the present invention, during each soldering, the residence time of the electric soldering iron on the cross section of the sample to be tested is preferably 5 to 8 seconds, more preferably 6 to 8 seconds. The present invention preferably controls the residence time of the electric soldering iron on the cross section of the sample to be tested within the above range, which not only realizes the soldering of the sample to be tested, but also saves time.
[0031] In the present invention, the pressure of each soldering is preferably 1-1.5 N, more preferably 1.5 N. In the present invention, preferably, a weight is hung on the front end of the electric soldering iron to realize pressurization of the sample to be tested, which is beneficial to avoid the influence of different operators on the test results. In the present invention, the distance between the hanging position of the weight and the end of the electric soldering iron is preferably 5-10 mm.
[0032] In the present invention, the multiple pressing preferably includes: performing the first pressing on the cross section of the sample to be tested, and then changing the pressing position for the next pressing, so that the angle formed by the positions of the Nth pressing and the N-1th pressing is ≤30°.
[0033] The present invention preferably changes the soldering position by rotating the electric soldering iron; the angle of each rotation is preferably ≤30°.
[0034] In the present invention, after the soldering is completed, if the deformation generated after each soldering on the cross section of the sample to be tested can be immediately restored after the electric soldering iron is removed, it is determined that the cross-linking degree of the UV cross-linked cable insulation layer to be tested is qualified; if at least one of the deformations generated after each soldering on the cross section of the sample to be tested cannot be restored after the electric soldering iron is removed, it is determined that the cross-linking degree of the UV cross-linked cable insulation layer to be tested is unqualified.
[0035] In the present invention, the method for judging whether the deformation of the sample to be tested cannot be restored is preferably: the difference in thickness between the sample to be tested after the electric soldering iron is removed and before soldering is ≥1 mm.
[0036] The present invention takes samples from both ends of the UV cross-linked cable to be tested, and then uses an electric soldering iron to solder the samples for multiple times until the entire cross section of the sample to be tested is pressed, and finally determines whether the degree of cross-linking of the insulation layer of the UV cross-linked cable to be tested is qualified by judging whether the deformation generated after each soldering on the cross section of the sample to be tested can be restored after the electric soldering iron is removed. The operation difficulty of operators and inspectors is greatly reduced, time is saved, the efficiency of finished product inspection is improved, product quality can be ensured, and the phenomenon of unqualified insulation cross-linking is completely eliminated.
[0037] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] UV cross-linked cable to be tested: Rated voltage 0.6 / 1kV copper core cross-linked polyethylene insulated wire core, nominal cross section 35mm 2 ;
[0040] (1) On a production line with a UV power of 90% and a line speed of 68 m / min, a production worker found that the end of the wire core deviated from the axis of the irradiation cavity when passing through the UV cross-linking equipment. In order to confirm whether the cross-linking degree of the wire core is qualified, samples were taken at both ends of the wire core to obtain the sample to be tested;
[0041] (2) The temperature of the automatic temperature-controlled soldering iron is set to 270°C and kept at a constant temperature for 5 minutes. A weight of 100 g (i.e., the soldering pressure is 1 N) is hung at a distance of 5 mm from the end of the soldering iron. Then, the hot soldering iron is used to perform the first soldering on the cross section of the sample to be tested obtained in step (1). The soldering pressure is kept for 5 seconds. Then, the soldering position is changed to perform the second soldering. The angle formed by the second soldering and the first soldering is 30°. The soldering position is changed and the soldering is repeated until the entire cross section of the sample to be tested is pressed. Twelve soldering points are obtained. It is found that two of the soldering points are concave and deformed by 1 mm after the soldering iron is removed, and the deformation cannot be restored to flatness, indicating that the cross-linking degree of the copper core cross-linked polyethylene insulated wire core is unqualified. The total time from sampling to result confirmation is 4 minutes.
[0042] Comparative Example 1
[0043] Sampling is performed at both ends of the wire core in Example 1 to obtain the sample to be tested; the sample to be tested is tested using the heat extension test method in GB / T2951.21-2008 "General test methods for insulation and sheath materials of electric and optical cables Part 21: Special test methods for elastomer mixtures - ozone resistance test - heat extension test - mineral oil immersion test";
[0044] The test results are: elongation under load 260% (standard requirement ≤ 175%), permanent deformation after cooling 25% (standard requirement ≤ 15%); it can be seen that the thermal extension test of the wire core in Example 1 does not meet the standard requirements (GB / T 12706.1-2020 "Rated voltage 1kV (U m =1.2kV) to 35kV (U m =40.5kV) Extruded insulated power cables and accessories Part 1: Rated voltage 1kV (U m =1.2kV) to 3kV(U m =3.6kV) extruded insulated power cable》), it was determined that the cross-linking degree of the core in Example 1 was unqualified; it took a total of 30 minutes from sampling to result confirmation.
[0045] Example 2
[0046] UV cross-linked cable to be tested: Rated voltage 0.6 / 1kV copper core cross-linked polyethylene insulated wire core, nominal cross-section 4×240+1×120mm 2 ;
[0047] (1) Sampling at both ends of the copper core cross-linked polyethylene insulated wire core to be tested to obtain a sample to be tested;
[0048] (2) The temperature of the automatic temperature-controlled electric soldering iron is set to 270°C and kept at a constant temperature for 5 minutes. A weight of 100 g (i.e., the soldering pressure is 1 N) is hung at a distance of 5 mm from the end of the electric soldering iron. Then, the hot electric soldering iron is used to perform the first soldering on the cross section of the sample to be tested obtained in step (1). The dwell time is 5 seconds. Then, the soldering position is changed to perform the second soldering. The angle formed by the second soldering and the first soldering is 30°. The soldering position is changed and the soldering is repeated until the entire cross section of the sample to be tested is pressed. 12 soldering points are obtained. After the electric soldering iron is removed, the concave deformations of the 12 soldering points are immediately restored to flatness, indicating that the cross-linking degree of the copper core cross-linked polyethylene insulated wire core is qualified. The total time from sampling to result confirmation is 8 minutes.
[0049] Comparative Example 2
[0050] The UV cross-linked cable to be tested in Example 2 was tested by the same test method as in Comparative Example 1, and the test results are shown in Table 1. According to the test results in Table 1, the thermal extension test of the UV cross-linked cable to be tested in Example 2 meets the standard requirements (the standard is the same as that in Comparative Example 1), thereby determining that the cross-linking degree of the UV cross-linked cable to be tested in Example 2 is qualified. It took a total of 50 minutes from sampling to result confirmation.
[0051] Table 1 Thermal extension test results of the UV cross-linked cable to be tested in Comparative Example 2
[0052]
[0053] Example 3
[0054] UV cross-linked cable to be tested: Rated voltage 0.6 / 1kV copper core cross-linked polyethylene insulated wire core, nominal cross section 150mm 2 ;
[0055] (1) On a production line with a UV power of 90% and a line speed of 57 m / min, a production worker discovered during a self-inspection during production intervals that the surface of the UV lamp was contaminated. The worker was concerned that the cross-linking degree of the insulated wire core produced was unqualified. To confirm whether the cross-linking degree of the wire core was qualified, he took samples from both ends of the wire core to obtain the sample to be tested.
[0056] (2) The temperature of the automatic temperature-controlled electric soldering iron is set to 270°C and kept at a constant temperature for 5 minutes. A weight of 100 g (i.e., the soldering pressure is 1 N) is hung at a distance of 5 mm from the end of the electric soldering iron. Then, the hot electric soldering iron is used to perform the first soldering on the cross section of the sample to be tested obtained in step (1). The dwell time is 5 seconds. Then, the soldering position is changed to perform the second soldering. The angle formed by the second soldering and the first soldering is 30°. The soldering position is changed and the soldering is repeated until the entire cross section of the sample to be tested is pressed. 12 soldering points are obtained. After the electric soldering iron is removed, the concave deformations produced by the 12 soldering points can be restored to flatness, indicating that the cross-linking degree of the copper core cross-linked polyethylene insulated wire core is qualified. The total time from sampling to result confirmation is 5 minutes.
[0057] Comparative Example 3
[0058] The UV cross-linked cable to be tested in Example 3 was tested by the same test method as in Comparative Example 1, and the test results were: elongation under load was 90%, and permanent deformation after cooling was 5%. It can be seen that the thermal extension test of the UV cross-linked cable to be tested in Example 3 meets the standard requirements (the standard is the same as that in Comparative Example 1), and thus it is determined that the cross-linking degree of the UV cross-linked cable to be tested in Example 3 is qualified. It took a total of 35 minutes from sampling to result confirmation.
[0059] It can be seen from the above embodiments and comparative examples that the results of testing the crosslinking degree of the UV-crosslinked cable insulation layer using the detection method provided by the present invention are consistent with the results of testing using the existing standard method, and the detection method provided by the present invention is time-saving and easy to operate.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for detecting the crosslinking degree of an ultraviolet crosslinked cable insulation layer, comprising the following steps: (1) Sampling at both ends of the UV-crosslinked cable to be tested to obtain a sample to be tested; (2) using an electric soldering iron to perform soldering and pressing on the cross section of the sample to be tested obtained in step (1) for multiple times until the entire cross section of the sample to be tested has been pressed; If the deformation caused by each soldering pressure on the cross section of the sample to be tested can be restored immediately after the soldering iron is removed, the cross-linking degree of the UV light cross-linked cable insulation layer to be tested is judged to be qualified; if the deformation caused by each soldering pressure on the cross section of the sample to be tested cannot be restored at least one place after the soldering iron is removed, the cross-linking degree of the UV light cross-linked cable insulation layer to be tested is judged to be unqualified.
2. The detection method according to claim 1, characterized in that: The cross-sectional area of the sample to be tested in step (1) is 25 to 500 mm 2 .
3. The detection method according to claim 1, characterized in that: The temperature of the electric soldering iron in step (2) is 270-280°C.
4. The detection method according to claim 1, characterized in that: During each soldering in step (2), the electric soldering iron stays on the cross section of the sample to be tested for 5 to 8 seconds.
5. The detection method according to claim 1, characterized in that: The pressure of each pressing in step (2) is 1 to 1.5N.
6. The detection method according to claim 1, characterized in that: The multiple soldering in step (2) includes: performing the first soldering on the cross section of the sample to be tested, and then performing the next soldering by rotating the electric soldering iron to change the soldering position, so that the angle formed by the position of the Nth soldering and the N-1th soldering is ≤30°.
7. The detection method according to claim 1, characterized in that: The method for judging whether the deformation of the sample to be tested cannot be restored in the step (2) is that the difference in thickness between the sample to be tested after the electric soldering iron is removed and before soldering is ≥1 mm.
Citation Information
Patent Citations
A method for characterizing the bending degree of a high-voltage crosslinked polyethylene cable
CN107101968A
Rapid preparation method of natural crosslinking insulation material
CN107192599A